2011
DOI: 10.1007/s12114-011-9088-0
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Returns to Graduating from a Historically Black College/University: Propensity Score Matching Estimates from the National Survey of Black Americans

Abstract: Black Colleges/Universities, Labor market outcomes, Matching estimators, I23, J01, J15,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…In terms of earnings and wages, while at least one analysis postulates a penalty for HBCU attendance (Fryer and Greenstone 2010), other evidence suggests no difference in earnings potential (Kim 2011) or even a benefit (Mykerezi and Mills 2008;Price et al 2011). On account of these figures and others like them, HBCUs have been deemed responsible for creating the black middle class (Drewry and Doermann 2001).…”
Section: Grand Outcome: Holistic Successmentioning
confidence: 99%
“…In terms of earnings and wages, while at least one analysis postulates a penalty for HBCU attendance (Fryer and Greenstone 2010), other evidence suggests no difference in earnings potential (Kim 2011) or even a benefit (Mykerezi and Mills 2008;Price et al 2011). On account of these figures and others like them, HBCUs have been deemed responsible for creating the black middle class (Drewry and Doermann 2001).…”
Section: Grand Outcome: Holistic Successmentioning
confidence: 99%
“…They are convinced that their data demonstrate that now "by some measures HBCU attendance appears to retard black progress" (U.S. Commission on Civil Rights 2010:126). These arguments, however, have been challenged and contradicted (Price et al 2011;Constantine 1995).…”
Section: Mismatch Mashupmentioning
confidence: 99%
“…Although I was supposed to be promoting Duke, I knew that graduates from HBCUs offer “a comparative advantage in nurturing the self‐image, self‐esteem, and identity of its graduates,” as well as “relatively superior long‐run labor market outcomes” (Price et al. :127).…”
Section: Introductionmentioning
confidence: 99%
“…Ceteris paribus, Black universities are more successful on average than other universities at graduating students (Ryan, 2004;Webber & Ehrenberg, 2010). Previous studies investigating labour market outcomes for Black universities' graduates had been mixed (Allen, 1992;Constantine, 1995;Strayhorn, 2008), but Price, Swinton, and Swinton (2011) showed that Black universities' graduates do enjoy a statistically significant earnings premium when selection issues are addressed. Black universities have been particularly successful in the sciences, having awarded more than 33 per cent of the science and engineering degrees earned by Black graduates nationally (Congressional Research Service, 2008).…”
Section: Introductionmentioning
confidence: 98%